A mathematical model for predicting the weight loss of packaged fruits - Yue He; Biao Lu; Xianqi Huang; Chi Feng (Applied Food Research, 2024)
The weight loss of fruits is important for distributors and consumers to determine the optimal storage and consumption time. Currently, the weight loss is determined primarily by experience without reliable guidance. In this study, a mathematical model based on the physical deduction of isothermal steady-state vapor diffusion process was proposed to predict the weight loss of postharvest packaged fruits. Experiments were conducted on three varieties of citrus fruits to verify the accuracy of the model. The results showed that the vapor diffusion resistance of the packaging bag was substantially higher than that of citrus fruit's peels, and that the weight loss of packaged citrus fruits was considerably lower than that of unpackaged controls during the entire storage period. The relative deviations of the predicted and measured weight loss at different storage periods for packaged Citrus sinensis Osbeck, Orah mandarin, and Citrus sinensis (L.) Osbeck were −4.68 % to 0.50 %, −3.93 % to 26.82 %, and −30.97 % to −14.39 %, respectively. These limited errors verify the predictive ability of the proposed model, which could also be applied to fruits and vegetables of other shapes - such as cylindrical - after minor modifications.